Campus Mental Health Revisited (Journal of Student Affairs in Africa, 2022)
This conceptual, reflective article explores recent innovations in mental health service provision at a large urban, residential university in South Africa during the COVID-19 pandemic. Prior to the pandemic, mental health services at this university were generally offered through face-to-face consultations, with secondary offerings in the form of well-being workshops at student residences and faculty houses. The need for mental health support was acute during the pandemic, placing great pressure on service provision. At the same time, however, everyone – that is, all staff and students – were working remotely as campuses had been closed under national lockdown. In this context, it was necessary to connect students to mental health services while they were studying remotely during the various phases of lockdown and to revisit the conventional and possibly largely reactive model of mental health service provision. Innovation in the promotion and provision of mental health services and products at this university, including through corporate partnerships and the responsible use of automation and technology, helped to achieve market penetration and widespread utilisation of services. In addition, ethical considerations; the factors inhibiting and supporting change; and the sustainability of the efforts undertaken during this period had to be addressed. Drawing lessons from the experience at this university, it is recommended that, while there will always be a place for conventional mental health service offerings, it may be time to expand the model permanently on modern campus environments, where there is a need for a caring community; committed leadership; the development of resilience in the student body; and the building of personal strengths in individuals.